The role of witchery and astrology programs in spreading illusion and myth - Khalaf Sabti, Muhammad; Khazal, Abdel Nabi (ALBAHITH ALALAMI, 2021)
« The emergence of satellite channels has led to fundamental changes in the supposed role of television, making it a center of culture and an important tributary to social upbringing and influencing the attitudes and values of individuals and in making public opinion regarding various issues, some television programs target ordinary people at home by virtue of the nature of their subjects, where there is a large audience of viewers, who consume and absorb what is offered to them from the cultural production of those satellite channels that play with the aspirations of groups of society to find metaphysical or magic solutions to their social problems or psychological delusions. The media, through its various messages, contributes to bringing about changes in the public’s understanding and comprehension of different issues and then directing them to deal with them and realize their goals, and this effect can appear in behavior. Therefore, this research sought to determine the cognitive, emotional and behavioral effects by watching those channels that display programs of witchery and astrology under the guise of verses of the Qur’an or what was called the prophetic medicine of religious amulet (for good luck in Islam) or herbal medicine, the research also sought to find out the reasons that lead the Iraqi individual to follow these channels, which is more influential on the Iraqi public and the relationship of the demographic variables of the respondents in the subject of exposure to it and the extent of the results achieved from that. The researcher used the survey method that aims to collect data and information from those under the research, relying on a questionnaire form designed to be a main tool for data collection, and through a multi-stage sample of (384) from the city of Baghdad.